Emotional intelligence in the work place (2017)
Every organizations in the world strive for enhanced productivity. To facilitate this, qualified professionals are recruited, trained and undergo retraining; adequate, relevant and modern technologies are utilized 'and close monitoring employed. However, many organizations have reported failure and inadequacies in their productivity and profit, possibly because many employees lack emotional intelligence skills, which could have helped them to navigate between their emotions and those of their employers and customers. This paper therefore focuses on the concept, rudiments, necessity, importance, components and application of emotional intelligence that could facilitate success in all human endeavours, especially at the workplace